Editorial - IFRS application in Central and South-Eastern European countries - Nadia Albu; Catalin Nicolae Albu (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The purpose of this paper is to introduce and reflect on the International Financial Reporting Standards (IFRS) application in Central and South-Eastern European (CSEE) countries, by providing an overview of IFRS research conducted in this geographical area, put in the context of the countries included. This special issue thus comprises the IFRS experience of eight countries: the Czech Republic, Estonia, Moldova, Poland, Romania, Slovenia, Turkey and Ukraine. Accounting research in these countries is in an incipient phase, and there is generally little information available in the international literature about accounting reforms and the manner in which international standards are applied, with a few exceptions.
Keywords: M41; 650; IFRS; developing countries; Central and South-Eastern Europe; literature review